Living Memories of an Eternal Legacy: Professor José Eduardo Lima Pinto da Costa - FREITAS, Ana Patrícia; PINTO DA COSTA, Maria José Carneiro de Sousa; FERRAZ, Amélia Assunção Beira Ricon (Revista Jurídica Portucalense, 2023)
José Eduardo Lima Pinto da Costa was born on the 3rd April 1934, in Cedofeita, Porto. The first son of José Alexandrino Teixeira da Costa and Maria Elisa Bessa de Lima Amorim Pinto, he became an outstanding figure in Legal Medicine. He graduated in Medicine and Surgery from the Faculty of Medicine of the University of Porto in 1960. He completed his mandatory military service, as a military doctor, in Cabinda, Angola. He doctorated in 1973, by presenting a dissertation on Legal Medicine, with a Complementary Test on Psychiatry. He was named Director of the Institute of Legal Medicine of Porto, in 1976, a position he held for twenty-five years, being until today the director with the longest term of office in that institution. Legal Medicine was Professor Pinto da Costa's great passion. He triggered decisive changes in this specialty and was a Master with disciples in multiple areas. He was a born communicator. A unique Professor. He transmitted his knowledge in a unique way. He knew how to captivate the audience. The magnetism of his speech and his knowledge marked several generations of students. He died on December 8, 2021, but his remarkable life and journey continue to be remembered and inspire those who had the privilege of meeting him.